Rabiniškoji hermeneutika, Tora ir Emmanuelio Levino judėjiško partikuliarizmo problema = Rabbinic hermeneutics, Torah and the problem of Emmanuel Levinas’ jewish particularism - Pažėraitė, Aušra Kristina (Religija ir kultūra, 2013)
In this paper, the constituents of the rabbinic hermeneutical approach to the Bible, which were important to Emmanuel Lévinas, are analysed through the theory of intertextuality. These constituents are the basic premise of priority of the text (Torah) and of the necessity of its interpretation by the interpretive community. The rabbinic notion of Torah as an Ur-text thus avoids logocentrism as well as the classical opposition Mythos / Logos in terms of the opposition Fiction / Truth. The concept of Mythos as a creation of imagination (as a metaphor or Story) that reveals the particularities enables one to involve it in the "universalizing" philosophical discourseas successfully as Greek myths were incorporated in the discourses of Ancient Greek philosophers. The author of this paper emphasizes that the "particularity" of Lévinas consists in the fact that his preferred "myths" in his Talmudic lectures and Judaic reflexions are driven from another source. Intellectual activity in Judaism as a "foundation of spiritual life" is based on hermeneutics which emphasizes the intellectual activity of the reader and presupposes the necessary polyphony of the "multiplicity of persons" with individual particular perspectives. The paper maintains that Lévinas, while discussing this hermeneutics (performing refined universalizations from these particularities), engages himself in the dialogue with the text, and this engagement can be seen as the hermeneutics of the reader whose particularity and historical context matters as well. For Lévinas, this hermeneutics allows him to use classical rabbinic texts, primarily the Talmud, as a potential source of concrete images for his philosophical thought, with the discussions of Talmudic sages serving as a guidance which may indicate the possible vectors of the meaning. Thus, the paper concludes that in the perspective of the theory of intertextuality, Lévinas is involved by these texts in the Jewish intertextuality, and this makes him part of the history of the Jewish Thought.